OPTIMALISASI LIMBAH KULIT BUAH RAMBUTAN MENJADI SUBKUTAN SEBAGAI PRODUK PANGAN YANG BERDAYA JUAL - Melani Putri Melati; Siti Nuraini; Yovita Aprilia Putri; Bagus Mardika; Agus Suyanto; Arum Suproborini (Universitas Lambung Mangkurat, 2019)
Rambutan (Nephelium lappaceum L.) is a seasonal fruit and is a native plant from Indonesia. No wonder if it's in the rambutan season, a lot of rambutan skin trash piles up on the road. This is certainly a problem if not addressed immediately. The purpose of this PKM is to save the environment from a pile of organic waste with new breakthroughs that are worth selling in increasing the growth of the creative economy. The new breakthrough is by processing rambutan skin into SUBKUTAN. The method of implementation in this PKM includes the planning, preparation of materials and materials, manufacturing of products, stages of promotion, marketing, and the evaluation phase with an implementation period of 5 months. The results of this PKM are SUBKUTAN candied products. We have marketed SUBKUTAN products both online and offline around Madiun, then we have also worked with various pharmacies, shops, and small shops. This product has various benefits that are good for health, specifically can reduce cholesterol, besides that this product has a fairly affordable price of Rp. 15,000.00. The output of our PKM is SUBKUTAN candied products, the publication of articles in the National Scientific Journal, final report, and progress report.